The crime of disclosure of bank secrecy and its criminal effects - العامري, سامر سعدون; عبد الله, كوثر عبد الرزاق (Journal of Legal Sciences, 2019)
The banking secret is a basic rule and the cornerstone of banking life, its historical roots are rooted in the history of ancient civilizations, and commitment to the capital attracts customers by ensuring that the bank keeps their business secret. This is important for the national economy ensure that the legislation regulates compliance with bank secrecy in its laws, making disclosure of the bank secret punishable, in addition to calculating the criminal effects on the bank employee, but also against the bank itself.